Diferentes métricas da diversidade de organismos planctônicos têm respostas distintas à adição experimental de nutrientes. - Dittrich, Jaqueline (2017)
Primary productivity is one of the main determinants of global biodiversity and it can be related to nutrient concentration in aquatic ecosystems. However, nutrient enrichment may alter the various components of biodiversity and ecosystem processes. The aim of this study was to evaluate plankton taxonomic and functional diversity responses to nutrient addition in microcosms. We experimentally established a gradient of nitrate and phosphate addition to ten treatments containing diverse assemblages of phytoplankton and zooplankton. Diversity was assessed based ontaxonomic (Shannon-Wiener Index, species richness and equitability) and functional diversity indexes (FRic, FDiv, FEve and RaoQ) for each microcosm (alpha diversity) and for each treatment (gamma diversity). Taxonomic and functional beta diversity were considered as the dissimilarity among replicates within each treatment; they were calculated with occurrence and species abundance data. We observed an increase in species richness and a decrease in equitability along the enrichment gradient for both groups, indicating the dominance of certain species in greater levels of productivity. Taxonomic beta diversity was positively related to nutrient gradient, pointing to the greater occurrence of stochastic processes in more rich microcosms. However, it also presented a dome relationship when abundance data were considered - greater species coexistence in intermediate levels of nutrient addition. Functional richness increased for both groups, whereas functional divergence decreased along the gradient, indicating that the excess of nutrients selects species with a certain combination of functional traits. We conclude that nutrient enrichment may affect biodiversity in a short period of time and at small spatial scales.